2007
DOI: 10.1051/vetres:2007041
|View full text |Cite
|
Sign up to set email alerts
|

Farm practices to controlE. coliO157 in young cattle - A randomised controlled trial

Abstract: -A randomised controlled trial was used to investigate the effect of three complex management intervention packages to reduce the burden of E. coli O157 in groups of young-stock on cattle farms in England and Wales. All intervention farms were assigned measures to avoid buying in new animals and having direct contact or sharing water sources with other cattle. Furthermore, package A (7 farms) aimed to keep a clean environment and closed groups of young-stock; package B (14 farms) aimed for improved water and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…A total of 411 farms distributed throughout England and Wales were contacted by phone to assess willingness to participate in the study and eligibility of the herd by questionnaire. Farms were eligible, if they retained more than 60 cattle including 20 young stock, had a bovine tuberculosisnegative status, and the premises were not shared with any public access enterprises such as open farms, Bed & Breakfast or farm-shops including selling unpasteurized milk (Ellis-Iversen et al, 2008).…”
Section: Examples Of Eligibility Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 411 farms distributed throughout England and Wales were contacted by phone to assess willingness to participate in the study and eligibility of the herd by questionnaire. Farms were eligible, if they retained more than 60 cattle including 20 young stock, had a bovine tuberculosisnegative status, and the premises were not shared with any public access enterprises such as open farms, Bed & Breakfast or farm-shops including selling unpasteurized milk (Ellis-Iversen et al, 2008).…”
Section: Examples Of Eligibility Criteriamentioning
confidence: 99%
“…The required samples sizes were 48 control farms and 48 farms in each intervention group to detect a risk ratio of 5 at 80% power with 95% confidence, when using a design effect of 13.22 to adjust for a group cluster size of 20 pat samples per group per visit. The design effect was estimated from data originating from a longitudinal study using the same sampling approach along with individual animal sampling (Ellis-Iversen et al, 2008).…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The review was limited by lack of high quality studies, inconsistent results, and conduct of studies in an artificial environment. One RCT not included in the SR showed improved hygiene (dry bedding and cohorting of animals by herd) decreased fecal shedding of E. coli O157 (P < 0.05) [41]. A recent RCT concluded that soil solarization in feeding pens significantly decreased E. coli O157: H7 contamination of soil (P < 0.05) [42].…”
Section: Resultsmentioning
confidence: 99%
“…General measures to control the spread and persistence of VTEC on the farm include good management and hygiene, clean and dry bedding, appropriate stocking rates, well-ventilated housing with good floor drainage, and practicing a closed herd policy (81,82).…”
Section: Control In Animal Wastementioning
confidence: 99%